Factors Associated With Treatment and Control of Hypertension in a Healthy Elderly Population Free of Cardiovascular Disease: A Cross-sectional Study. (6th December 2019) - Chowdhury, Enayet K; Nelson, Mark R; Ernst, Michael E; Margolis, Karen L; Beilin, Lawrence J; Johnston, Colin I; Woods, Robyn L; Murray, Anne M; Wolfe, Rory; Storey, Elsdon; Shah, Raj C; Lockery, Jessica E; et al.
Abstract: BACKGROUND: Despite readily available treatments, control of blood pressure (BP) with population aging remains suboptimal. Further, there are gaps in the understanding of the management of high BP in the aged. We explored antihypertensive treatment and control among elderly hypertensive participants free from overt cardiovascular disease (CVD), and identified factors related to both "untreated" and "treated but uncontrolled" high BP. METHODS: We analyzed baseline data from 19, 114 individuals aged ≥65 years enrolled from Australia and United States (US) in the ASPirin in Reducing Events in the Elderly study. Hypertension was defined as an average systolic/diastolic BP ≥140/90 mm Hg and/or the use of any BP lowering medication. "Controlled hypertension" was defined if participants were receiving antihypertensive medication and BP <140 and 90 mm Hg. Descriptive analyses were used to summarize hypertension control rates; logistic regression was used to investigate relationships with treatment and BP control. RESULTS: Overall, 74% (14, 213/19, 114) of participants were hypertensive; and of these 29% (4, 151/14, 213) were untreated. Among those treated participants, 53% (5, 330/10, 062) had BP ≥140/90 mm Hg. Participants who were untreated were more likely to be men, have higher educational status, and be in good physical health, and less likely to have significant comorbidities. The factors related to "treated but uncontrolled" BP included older age, male, Black race (vs. White), using antihypertensive monotherapy (vs. multiple) and residing in Australia (vs. US). CONCLUSIONS: High levels of "untreated" and "treated but uncontrolled" BP occur in healthy elderly people without CVD, suggesting there are opportunities for better BP control in the primary prevention of CVD in this population. CLINICAL TRIALS REGISTRATION: NCT01038583.